Natural Compounds and Their Small Molecule Derivatives as PI3-Kinase Inhibitors against Cancer - Ali, Abuzer; Ali, Amena (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Earlier findings revealed the importance of different natural compounds and synthetic drugs in the treatment of cancer by targeting Phosphoinositide 3-Kinase (PI3K). In the direction to discover novel PI3K inhibitors, the present study includes the generation of fragment derivatives. Natural compounds and FDA-approved synthetic drugs were selected for screening against PI3K by using different computational methodologies. Materials and Methods: The top ranked compounds dehydroglyasperin D, honokiol and quercetin were taken for generation of derivatives and 30 (out of 300) derivatives were screened with less than 2 synthetic accessibility scores. The ADME property predictions were also performed. Results: The top ranked derivatives of honokiol (15_Hono-1) and dehydroglyasperin D (40_Dehydro-2) showed the best binding interactions, with docking scores of -10.09 and -8.61 Kcal/mol, respectively. Further, the PASS prediction coefficient with tumor cell lines and non-tumor cell lines showed the importance of derivatives action against tumor. The pharmacophore modeling determined the important interactive sites with receptors and MMGBSA method was used for rescoring of docking poses. Based on the results, honokiol and dehydroglyasperin D derivatives may become efficient lead compounds as PI3K inhibitors against cancer. Conclusion: The study is based on the screening of potent compounds as PI3K inhibitors. The screened compound showed similar binding interactions as reference ligand. The screened compounds have drug-likeness properties. The study may be beneficial for researchers in the development of natural compounds as PI3K inhibitors for the treatment of cancer.
Keywords: Cancer; Dehydroglyasperin D; Honokiol; Molecular docking; Phosphoinositide; 3-kinase; PI3K inhibitor